Evolutionary history of novel genes on the tammar wallaby Y chromosome: Implications for sex chromosome evolution - Murtagh, Veronica J.; O'Meally, Denis; Sankovic, Natasha; Delbridge, Margaret L.; Kuroki, Yoko; Boore, Jeffrey L.; Toyoda, Atsushi; Jordan, Kristen S.; Pask, Andrew J.; Renfree, Marilyn B.; Fujiyama, Asao; Graves, Jennifer A. Marshall; et al. (Genome Research, 2012)
We report here the isolation and sequencing of 10 Y-specific tammar wallaby (Macropus eugenii) BAC clones, revealing five hitherto undescribed tammar wallaby Y genes (in addition to the five genes already described) and several pseudogenes. Some genes on the wallaby Y display testis-specific expression, but most have low widespread expression. All have partners on the tammar X, along with homologs on the human X. Nonsynonymous and synonymous substitution ratios for nine of the tammar XY gene pairs indicate that they are each under purifying selection. All 10 were also identified as being on the Y in Tasmanian devil (Sarcophilus harrisii; a distantly related Australian marsupial); however, seven have been lost from the human Y. Maximum likelihood phylogenetic analyses of the wallaby YX genes, with respective homologs from other vertebrate representatives, revealed that three marsupial Y genes (HCFC1X/Y, MECP2X/Y, and HUWE1X/Y) were members of the ancestral therian pseudoautosomal region (PAR) at the time of the marsupial/eutherian split; three XY pairs (SOX3/SRY, RBMX/Y, and ATRX/Y) were isolated from each other before the marsupial/eutherian split, and the remaining three (RPL10X/Y, PHF6X/Y, and UBA1/UBE1Y) have a more complex evolutionary history. Thus, the small marsupial Y chromosome is surprisingly rich in ancient genes that are retained in at least Australian marsupials and evolved from testis–brain expressed genes on the X.